Synthesis and characterization of tin sulfide nanomaterials and thin films by pulsed laser ablation in liquid. - Johny, Jacob (2019)
Tin monosulfide (SnS) and tin disulfide (SnS2) nanoparticles were synthesized by employing pulsed laser ablation in liquid (PLAL) technique in various organic solvents where the influence of different laser parameters and solvents were investigated. Spray deposition technique has been implemented as a method to fabricate thin films of these materials where the spray parameters were optimized depending on the solvent and material. Combination of pulsed laser ablation in liquid with spray technique was used for the first time in the work. In the case of SnS nanoparticles, they were first prepared by laser ablation in isopropanol and N,N-dimethyl formamide and thin films of the same were deposited by spraying the laser generated nanocolloids onto heated substrates where the films fabricated were characterized for their structure, morphology and opto-electronic and electrochemical properties. Moreover, colloidal graphene oxide was mixed with SnS nanocolloids at different volume concentrations (0.1%, 0.5% and 1%) to obtain SnS: GO or SnS: rGO thin films where the nanocomposite films showed enhanced opto-electronic and electrochemical properties compared to the pristine SnS thin films. A solar cell configuration of glass/ CdS/ Sb2S3/ SnS:rGO was also fabricated using the SnS: rGO layer as the absorber and photoconversion efficiency of 2.3% was achieved. In the case of SnS2 nanoparticles, effect of four different solvents (acetone, isopropanol, ethanol and DMF) and two different laser wavelengths (1064 nm and 532 nm) on the morphologies and properties of SnS2 particles were studied in detail. Furthermore, influence of ablation fluence, liquid medium temperature and post irradiation on the SnS2 nanoparticles were investigated in detail and the hydrogen evolution activity of these nanoparticles were tested in acidic medium. Electrochemical properties of the SnS2 thin films deposited from SnS2 nanoparticles in ethanol and isopropanol and after different post annealing treatments (200, 250 and 300 ℃) were analyzed and the results were compared. For majority of the cases, the prepared nanoparticles and thin films were analyzed for their structure, crystalline nature, composition and morphology by XRD, Raman, XPS, TEM and SEM whereas the optical, opto-electronic and electrochemical properties were elucidated using the UVVisible spectroscopy, I-V measurements under dark and illumination and electrochemical measurements respectively.